Pathophysiology of spontaneous coronary artery dissection: hematoma, not thrombus - Djokovic, Aleksandra; Krljanac, Gordana; Matic, Predrag; Zivic, Rastko; Djulejic, Vuk; Marjanovic Haljilji, Marija; Popovic, Dusan; Filipovic, Branka; Apostolovic, Svetlana (Frontiers in Cardiovascular Medicine, 2023)
Spontaneous coronary artery dissection (SCAD) accounts for 1.7-4% of all acute coronary syndrome presentations, particularly among young women with an emerging awareness of its importance. The demarcation of acute SCAD from coronary atherothrombosis and the proper therapeutic approach still represents a major clinical challenge. Certain arteriopathies and triggers are related to SCAD, with high variability in their prevalence, and often, the cause remains unknown. The objective of this review is to provide contemporary knowledge of the pathophysiology of SCAD and possible therapeutic solutions.